Evaluating the outdoor thermal comfort conditions in urban villages of Kuala Lumpur / Pegah Maroofee - Pegah , Maroofee (2017)
Urban villages (kampungs) are distinctive products of rapid urbanization and massive rural to urban migration, located within cities and surrounded by high rise buildings. These urban villages have still kept their own design patterns and characteristics. Kuala Lumpur (KL) still has some traditional urban villages that have not been replaced by contemporary residential projects due to the rapid modernization and urban growth. Although thermal comfort of outdoor urban spaces is an influential factor in residential behavior, there is a limited number of studies that have been conducted especially in KL city. On the other hand, this is a significant factor in increasing the use of outdoor spaces and preserve traditional conditions. This study measures and reports a quantitative research of the field measurements and simulates the collected data from experimental study via the Rayman and ENVI-met softwares. The purpose of this simulation is to evaluate the outdoor thermal comfort in both shaded and unshaded areas in urban villages in hot and humid climate. Three different areas of KL city namely Kampung Baru, Kampung Melayu Kepong, and Kampung Sungai Penchala were chosen based on geographically location in regards with clarifying differences in the environment surrounding, identification of natural environments such as vegetation, material and surface, and the level of density. Physiological Equivalent Temperature (PET) and Mean Radiant Temperature (Tmrt) indices were used to explore the functional spaces of the selected areas towards identifying the climatological condition in outdoor spaces and the significant environmental values to achieve a higher level of quality of life. The findings of field measurement results show that among the shaded areas, Kampung Melayu Kepong recorded the coolest weather at 11:00 am with 27.7oC while the warmest was the Kampung Baru at 16:00 pm with 34.9 oC; whereas, in unshaded areas Kampung Melayu Kepong with 30.5 oC and Kampung Sungai Penchala with 37 oC were coolest and warmest respectively. In terms of wind speed, Kampung Melayu Kepong recorded the fastest speed with 3.28 m/s blew from the southeast. Kampung Melayu Kepong and Kampung Sungai Penchala have the highest measured relative humidity of 78%, and coolest temperature of 27.7oC, and 26.2oC respectively. According to ENVI-met simulation in the shaded area, the coolest kampung was Kampung Melayu Kepong with 25.59 oC; whereas, the warmest was Kampung Baru with the highest recorded temperature of 34.8 oC. In addition, the highest temperature in the unshaded area measured was Kampung Baru with 35.38 oC, and the lowest temperature was in Kampung Melayu Kepong recorded 30.12 oC. In summary, the results show that the higher relative humidity percentage decreases temperature. Moreover, this research proposes some effective technological and specialized suggestions on the appropriate design to promote outdoor thermal comfort satisfaction, mitigation of heat in hot and humid context and having a better quality of life.